Mullerian adenosarcoma of the uterus with MASO: a case report of cervical adenosarcoma in a young female that never had sexual behavior - Jia-Wei Chen; Ya-Jie Huang; Ling-Lu Wang; Jun-Jiang Liu; Ming-Mei Shi; Na Li (BMC, 2024)
Abstract Background Cervical mullerian adenosarcoma is a rare uterine sarcoma, especially in young women. Its pathological features are low-grade malignant tumors with bidirectional differentiation, and the degree of malignancy is similar to that of low-grade endometrial stromal sarcoma. This paper reports the case of a young asexual patient who has been closely followed up after tumor resection and has not had any recurrences. Case presentation A 20-year-old, young asexual woman was diagnosed with cervical mullerian adenosarcoma with sarcomatous overgrowth (MASO). Cervical tumor resection was performed after admission, and the resection margin was negative. After the operation, she refused to undergo secondary surgery due to fertility requirements and did not receive adjuvant treatment. The patient was closely followed up after the operation and has not yet relapsed. Conclusion A young woman with cervical MASO did not receive adjuvant treatment after cervical tumor resection. For women with fertility requirements, close follow-ups should be conducted after the operation to guard against tumor recurrence and radical tumor resection should be performed as early as possible after the patient no longer requires their fertility.